THE ROLE OF PRAGMATICS COMPETENCE IN SUPPORTING STUDENT'S SELF-ESTEEM IN ENGLISH LANGUAGE LEARNING - Muzayyanah, Nafilatul; Nurjati, Nunung; Syahria, Nukmatus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research investigates the role of pragmatic competence in supporting students' self-esteem in English language learning, employing a Mixed Methods approach with an Exploratory Sequential Mixed-Methods Design. The study was conducted with 80 students from Secondary School. The first phase utilized a quantitative Likert scale questionnaire to measure the relationship between pragmatic competence and self-esteem. The second phase involved qualitative narrative analysis from interviews with students and teachers to gain deeper insights. Results indicate that students with higher pragmatic competence, such as using politeness strategies and contextually appropriate responses, demonstrated increased self-esteem. Internal factors such as motivation and past experiences, and external factors including family support and teacher feedback, were found to influence this relationship. The study highlights the importance of enhancing pragmatic competence through collaborative learning, self-reflection, and creating a supportive environment to boost students' confidence and willingness to engage in English language activities. This research provides recommendations for integrating pragmatic competence into English teaching to promote both language skills and self-esteem.